ANALISIS KARAKTERISTIK DAN KEBUTUHAN PARKIR DI PASAR PABEAN SEDATI - Fadel Ibrahim; Nurani Hartatik (LPPM Universitas Bina Bangsa, 2023)
Parking is an important component in the needs of the transportation system so the need for parking spaces must be known before planning the construction of for example traditional markets. The market is one of the economic sectors that is a place to interact between sellers and buyers, one of which is the Sedati Customs Market. Parking spaces at the Sedati Customs market cannot accommodate vehicles during peak hours due to lack of parking space. This study aims to analyze parking characteristics, parking capacity, and parking space needs in the Sedati Customs market. Based on the results of research conducted from Monday, May 1, 2023 to Sunday, May 7, 2023, it was found that the maximum accumulation occurred on Saturday, May 6, 2023 at peak hours, namely 07.00 – 08.00 of 35 vehicles. The vehicle volume on the peak day, Saturday, May 6, 2023, reached 327 vehicles. The percentage of parking index from Monday, May 1, 2023 to Sunday, May 7, 2023 has exceeded 100%, indicating that parking capacity is not enough to accommodate incoming vehicles. The parking capacity owned by the Sedati Customs market is only 20 SRP while the required capacity is based on a maximum accumulation of 35 vehicles. Parking needs at the Sedati Customs market found that parking spaces require 15 more SRP in order to accommodate vehicles during peak hours